The Effect of Tax Expenses, Tunneling Incentives, and Level of Debt on Transfer Pricing - Wulandari Agustiningsih; Gebrina Riski; Eny Purwaningsih; Hermanto Hermanto; Menik Indrati (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
This study examine effect of tax expenses, tunneling incentives and leverage on transfer pricing. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. Sampling was determined using purposive sampling in order to obtain a sample data of 22 from 179 population data. The type of data used is secondary data obtained from the website www.idx.co.id.  The analytical method used is multiple regression analysis. The results shown in this study indicate that tax expense and leverage do not have a significant effect on transfer pricing while tunneling incentives have a significant positive effect on transfer pricing.